Analisis tentang Setting Roller Gauge dan Break Draft Tidak Merubah Total Draft pada Mesin Roving Rieter type F10 / 55011- 00425 Tahun Pembuatan 1998 - Yulianto, Bambang (Akademi Komunitas Industri Tekstil Dan Produk Tekstil Surakarta, 2020)
At PT Indiratex Spindo, there are 2 units that produce 100% cotton yarn. For unit 1 produces open end yarn, and for unit 2 produces ring spinning yarn. The production process in unit 2 starts from the raw material, namely cotton in the blowroom process, opening and mixing of the cotton so that the shape of the feathers will be processed in the carding machine to further open cotton fibers, clean dirt and short fibers with long fibers. The result of the card is that the card sliver will then be duplicated and drafted on the draw frame breaker, after which it will be processed and duplicated again in the finisher draw frame. Then the sliver drawing finisher will be drafted, given a twist and rolled in a bobbin on the roving machine. The output of the roving machine will then be processed in the ring spinning machine, the roving will be drafted, twisted so that the yarn will then be rolled into the cop, then put in the winding machine to remove thread imperfections or yarn defects and change the cop roll to cones rolls. After the process is complete, the thread will be packed in the packing section. To produce good quality yarn, it is necessary to plan production, repair and maintenance as well as repair machines properly. Drafting is one one process that is very important and to be hard to the quality of the yarn that will be produced. If the drafting process is not perfect it will affect the unevenness of the material or yarn. One of the problem topics related to drafting on the Rieter type F10 / 55011-00425 roving machine in 1998 is that if the break draft is changed, the total draft will change. This assumption is really true because if the draft is damaged, what will change is the main draft, and the total draft will remain the same. Meanwhile, for the correct setting of the roller gauge so that the roving does not experience a high level of unevenness, if the setting is wide, the draft break must be small. And if the arrangement is eternal then the break draft used must be large. The second arrangement is so that the fiber can be properly drafted and does not experience floating fibers or fiber cracks.